Kajian Eco Driving pada Bus Rapid Transit Koridor VI untuk Mendukung Konsep Transportasi Berkelanjutan di Kota Semarang - Yovita Nuri Putri; Yudi Basuki (Jurusan Perencanaan Wilayah dan Kota, 2018)
BRT is one of the mass transportation facilities that has the main function of serving human movement. The existence of BRT can also be used as an alternative besides of personal transportation. To maintain sustainability, BRT needs to apply eco driving. In addition to maintaining the sustainability of the bus, the application of eco driving can also reduce emissions and to save fuel consumption. Emission of released gases can have a negative impact on the environment in the long term whereas excessive fuel consumption can have an impact on the economy if fuel is starting to be difficult to obtain. The application of eco driving is also one way to support the concept of sustainable transportation in its particular urban area on the economic and environmental aspects. The concept cannot run properly if the driver does not apply eco driving. Due to the absence of eco driving can trigger drivers not to behave economically in driving so it gives impact the increase in emissions, excess fuel consumption and affect the sustainability or durability of the bus.This research has a purpose to assess the operational of BRT corridor VI in Semarang City based on eco driving rule. To achieve these purpose, it is necessary to analysis of eco driving level based on BRT corridor VI, analysis of eco driving level based on BRT driver corridor VI and analysis of eco driving indicator not applied by BRT driver corridor VI. Analysis done by using data result from field observation called checklist data. The checklist data that has been obtained will be given a score where the eco driving indicator applied is given a score of 1 whereas that is not applied given a score of 0. Assessment is done on 16 drivers and for each driver is done assessment on 26 stops or segment. The results of the assessment will be summed and processed to obtain the category of eco driving.The results of the analysis show that the level of eco driving in BRT corridor VI is classified as medium. This means that the concept of sustainable transportation has been implemented but not fully yet. This is because 14 of the 16 drivers classified as medium eco driving are still not fully implementing eco driving. Indicator of eco driving that is still often done by the driver is sudden braking, unstable speed, unnecessary accelerate and unnecessary deceleration. These four indicators occupy four major eco-driving indicators that are not appropriate with the concept of sustainable transportation, especially on economic aspects because it can affect the efficiency of fuel consumption and sustainability or durability of the bus.